PSYCHOLOGICAL HAPPINESS AMONG PHYSICAL EDUCATION AND SPORTS SCIENCES STUDENTS AT UNIVERSITY OF MAYSAN - Sadiq Ibrahim Abdullah; Wissam Halil Manati (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Psychological happiness is a dynamic state that reflects an individual’s sense of will, ambition, self-confidence, self-awareness, and ability to grow and adapt. In the context of physical education and sports sciences, such psychological traits are essential, as students often demonstrate optimism, perseverance, a sense of responsibility, and interpersonal skills that contribute to their overall well-being. Objectives. This study aimed to identify the level of psychological happiness among students of physical education and sports sciences at the University of Maysan and to construct a reliable and valid measurement scale for assessing this construct. Method. The research employed a descriptive survey design. The study population consisted of 488 male and female students enrolled in the Faculty of Physical Education and Sports Sciences at the University of Maysan. A total of 300 students (61.48% of the population) were selected as the research sample. The researchers developed a psychological happiness scale, and statistical analyses were performed using SPSS software to assess the scale’s validity, reliability, and to determine standard levels. Results. The findings revealed that students in the physical education and sports sciences program at the University of Maysan demonstrated a generally high level of psychological happiness. The developed scale showed acceptable psychometric properties. Conclusion. Students of physical education and sports sciences at the University of Maysan are characterized by positive psychological well-being. The study recommends conducting similar research at other Iraqi universities to further understand and support student mental health in this academic field.